Hyperechoic Lesions on Breast Ultrasound: All Things Bright and Beautiful? - Ramani, S. K.; Rastogi, Ashita; Nair, Nita; Shet, Tanuja M.; Thakur, Meenakshi H. (Indian Journal of Radiology and Imaging, 2021)
Ultrasound (US) lexicon of the Breast Imaging Reporting and Data System (BI-RADS) defines an echogenic breast mass as a lesion that is hyperechoic in comparison with subcutaneous adipose tissue. However, at sonography, only 0.6 to 5.6% of breast masses are echogenic and the majority of these lesions are benign. approximately, 0.5% of malignant breast lesions appear hyperechoic. The various benign pathologic entities that appear echogenic on US are lipoma, hematoma, seroma, fat necrosis, abscess, pseudoangiomatous stromal hyperplasia, galactocele, etc. The malignant diagnoses that may present as hyperechoic lesions on breast US are invasive ductal carcinoma, invasive lobular carcinoma, metastasis, lymphoma, and angiosarcoma. Echogenic breast masses need to be correlated with mammographic findings and clinical history. Lesions with worrisome features such as a spiculated margin, interval enlargement, interval vascularity, or association with suspicious microcalcifications on mammography require biopsy. In this article, we would like to present a pictorial review of patients who presented to our department with echogenic breast masses and were subsequently found to have various malignant as well as benign etiologies on histopathology.
Keywords: breast ultrasound; hyperechoic breast mass; mammography